2009
DOI: 10.2165/11316930-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligodeoxyneucleotides as TLR9 Agonists

Abstract: Toll-like receptors (TLRs) are part of the innate immune system, and they belong to the pattern recognition receptors (PRR) family. The PRR family is designed to recognize and bind conserved pathogen-associated molecular patterns, which are not generated by the host and are restricted and essential to micro-organisms. TLR9, which recognizes unmethylated CpG (cytosine guanosine dinucleotide), is a very promising target for therapeutic activation. Stimulation of TLR9 activates human plasmacytoid dendritic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 120 publications
0
35
0
Order By: Relevance
“…Except as a vaccine adjuvant, numerous studies established that systemic delivery of free CpG is ineffective in eliciting anti-tumor immunity (8, 10, 13, 14, 18). chTNT-3/CpG1585 and chTNT-3/1826 monotherapies likely delayed tumor growth and improved survival by delivering the CpG moiety to the tumor, and may have increased CpG half-life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except as a vaccine adjuvant, numerous studies established that systemic delivery of free CpG is ineffective in eliciting anti-tumor immunity (8, 10, 13, 14, 18). chTNT-3/CpG1585 and chTNT-3/1826 monotherapies likely delayed tumor growth and improved survival by delivering the CpG moiety to the tumor, and may have increased CpG half-life.…”
Section: Resultsmentioning
confidence: 99%
“…Intratumoral injections of CpG elicited immune responses against tumors in murine models of melanoma (710), fibrosarcoma (7), renal cell carcinoma (8), colon adenocarcinoma (8, 9, 11), pancreatic adenocarcinoma (11), neuroblastomas (12), and lymphoma (13). Following its success in preclinical models, CpG were used in clinical trials for a wide range of cancers (reviewed in (14, 15)). However, optimal therapeutic effects were generally limited to intratumoral injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this trial was initiated, Slingluff and colleagues reported that the inclusion of GM-CSF with Montanide may result in diminished peptide-induced T cell responses in a melanoma vaccine study [34]. The TLR agonists CpG 7909 and polyIC:LC have recently been explored and should continue to be investigated as a possible adjuvant [35]. The MAGE-3 protein-based vaccine from GSK-Bio utilizes a combination of the TLR9 agonist CpG7909 and the TLR4 agonist MPL [36].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 This mechanism further triggers cell signaling pathways, such as mitogen-activated protein kinases and NFκB, which induce multiple proinflammatory cytokines and chemokines Thus, CpG ODNs are promising immune adjuvants and immunotherapeutic agents against allergy/asthma, cancer, and infectious diseases. [11][12][13][14] Clinical studies suggest that CpG ODNs are safe and well tolerated when administered to humans; these molecules reportedly improve vaccineinduced immune responses. 2,15 However, the biologic activity of CpG ODNs is transient, and the extreme susceptibility to nuclease degradation in serum and poor cellular uptake of natural CpG ODNs severely limit the therapeutic applications of these molecules.…”
Section: Introductionmentioning
confidence: 99%